A teaching strategy for dyslexic children: utilising a multi-sensory approach / Norarifah Ali ... [et al.] - Ali, Norarifah; Md Hashim, Azhari; Abdullah, Mohamad Hariri; Yaakob, Muhammad Nidzam; Alias, Roslinda (Universiti Teknologi MARA, Kedah, 2023)
Early detection of learning difficulties, such as dyslexia, in children aged 5 and below is crucial to provide them with the appropriate attention and support in developing essential skills such as letter recognition, spelling, and reading. Dyslexic children often struggle with spelling, highlighting the need for effective interventions. This study aimed to evaluate the effectiveness of the Smart Board, a teaching tool, in assisting beginner-level dyslexic children in developing simple Malay syllables. The intervention utilised a multi-sensory approach, incorporating kinesthetic, auditory, visual, and tactile senses to teach students how to form basic Malay syllables using lowercase letters. The research was conducted at the DAM Centre Pulau Pinang Branch, DAM Centre Sg. Petani Branch, and SK Bukit Kiara Kedah in Malaysia. The findings have indicated positive outcomes from the use of the Smart Board as a teaching tool. The participants showed improvement in recognising letters, forming syllables, rewriting accurately, and spelling correctly. The multi-sensory approach of the Smart Board enhanced their understanding and application of basic Malay syllables The results support the effectiveness of the Smart Board in assisting dyslexic children at the beginner’s level. The multisensory approach, integrating kinesthetic, auditory, visual, and tactile elements, successfully addressed spelling difficulties. The interactive and engaging nature of the Smart Board facilitated the participants' learning experience and contributed to their progress in building basic Malay syllables. The study highlights the efficacy of the Smart Board as an intervention for beginner-level dyslexic children in developing simple Malay syllables. Proper utilisation of the Smart Board in dyslexia centres, schools, and therapeutic facilities is essential to maximise its benefits. Future research should focus on investigating teaching aids for dyslexic children at intermediate and advanced levels, expanding the available resources for their education.